Aqueous solution of Oxone as new oxidizing agent for multi-walled carbon nanotube functionalization. Issue 5 (4th May 2017) - Tavakoli, Akram; Babaluo, Ali Akbar; Safaee, Khadijeh
ABSTRACT: In this work, multi-wall carbon nanotube (MWCNT) was successfully modified using aqueous solution of Oxone as a new oxidant. The effect of oxidation temperature on various characteristics of the treated MWCNTs was also investigated. FTIR and titration analysis proved the formation of carboxyl, carbonyl and epoxide groups at the surface of MWCNTs. The concentration of the functional groups increased as the modification temperature increased. The presence of such oxygen containing groups at the surface of MWCNTs justified the long time stability of the treated MWCNTs suspensions in water and methanol. The modified MWCNTs showed higher entanglement compared to row MWCNT due to the cross-links adjacent effect of pendant functional groups. Finally, it was concluded that Oxone oxidation process destroys the structure of the MWCNTs, but not severe enough to unzip the MWCNTs.